Analysis of Various Factors Associated with Antenatal Care Visits - Yoseph Rani Riberu; Andreas Umbu Roga; Rafael Paun (Jurnal Penelitian Pendidikan IPA, 2023)
Antenatal care is a service provided to pregnant women from conception to the beginning of childbirth in accordance with antenatal service standards. The purpose of this study is to identify predisposing factors (knowledge and attitudes), social capital (social capital) and geographical factors (mileage, location, travel time, transportation path and cost). This study uses a survey method or descriptive correlation with a cross sectional approach. With a total sample of 85 respondents with a simple random sampling technique. Research instruments using questionnaires and data analysis techniques to achieve linear regression to see simultaneously related factors. From the results of the study, it was found that there was a relationship between predisposing factors; knowledge (p value 0.000<0.005) and attitude (p value 0.000<0.005) with antenatal care visits. The existence of a relationship between social factors of capital; Trust (P Value 0.026<0.005), Reciprocity (P Value 0.019<0.005), NormA (P Value 0.009<0.005) With Antenatal Care Visits. The existence of a relationship between geographical factors; mileage (p value 0.947>0.005), location (p value 0.043<0.005), travel time (p value 0.272>0.005), transpotation path (p value 0.977>0.005) and cost (p value 0.021<0.005) with antenatal care visits. The most dominant factor in the relationship with antenatal car visits is the level of knowledge and attitude with an equation level of p=0.52 (52%). Â